Spy school goes north a spy school novel - Gibbs, Stuart (New York Simon & Schuster Books for Young Readers, 2023)
"Ben Ripley and his friends are training in Alaska when Cyrus Hale is kidnapped by his old Russian nemesis. Ben, Erica, and the others mount a rescue mission, but events quickly spiral out of control in a plot involving the secret history of US-Russian relations, a young KGB agent with skills to rival Erica$1 (Bs$1 (Band lots and lots of bears" --s
Ages 8-12.
Grades 7-9.
112350
Keywords: Middle school students -- Juvenile fiction; Schools -- Juvenile fiction; Kidnapping -- Juvenile fiction; Rescues -- Juvenile fiction; Spies -- Juvenile fiction; Alaska -- Juvenile fiction; Action and adventure fiction; Fiction; Juvenile works; Novels; School fiction; Spy fiction; Spy stories